Report on Public Sector Undertakings - Administrative Reforms Commission (Administrative Reforms Commission, Government of India)
The rapid achievement of economic progress has been the major objective of governmental policy and action since India won freedom in 1947. Economic development before Independence was largely left to the efforts of the private sector, and the role of the State was confined to providing the essential economic infra-structure. The position has changed radically since then. There has been a rapid and considerable expansion of the public sector. Public enterprises have assumed a key role in the economy of the country and their performance will now largely determine the speed and effectiveness with which we can achieve our social and economic goals.
Administrative Reforms Commission, Government of India